Measuring Bilateral Market Power in International Markets of Vertically Differentiated Agricultural Commodities - Yamaura, Koichi; Xia, Tian (My University, 2017)
Two features of international markets of agricultural commodities are bilateral market power of exporting and importing countries and the coexistence of non-genetically modified (non-GM) and genetically modified (GM) products. The two features were not taken into account in most extant studies on market power in international agricultural commodity markets. This research develops a bilateral oligopoly model with the interaction between non-GM and GM commodity and conducts an empirical estimation for U.S.-Japan soybean trade. The estimation results show that U.S. exporters and Japanese importers are almost equally sharing the dominance of market power. The analysis in this research provides new measures of market power and improves the understanding on world soybean markets. © 2016 by De Gruyter 2016.
Citation: Yamaura, K., & Xia, T. (2016). Measuring Bilateral Market Power in International Markets of Vertically Differentiated Agricultural Commodities. Journal of Agricultural and Food Industrial Organization, 14(1), 33-42. doi:10.1515/jafio-2013-0020
Keywords: Bilateral Oligopoly; Market Power; Non-Gm Soybeans; Vertically Differentiated Products